A Sociocultural Examination of Religiosity's Role in Coupon Proneness - Ding, William; Sprott, David; Joireman, Jeff (Psychology and Marketing, 2026)
Keywords: Consumer behaviour; Coupon; Face (sociological concept); Religiosity; Revenue; Sociocultural evolution; Survey data collection; benevolent inference; coupon proneness; dept.mrk; mixed method; religiosity; sociocultural variables

Beyond algorithm aversion: The impact of psychological readiness on algorithmic advice - Kim, H. (Computers in Human Behavior, 2025)
Keywords: Advice (programming); Advice-taking; Algorithm appreciation; Algorithm aversion; Matching (statistics); Mindset; Openness to experience; Psychological readiness; Trust; Uncertainty; dept.mrk

A systematic investigation of why P2P services are rated higher than traditional services - Unnava, Vasu; Singh, Amit Surendra; Unnava, H. Rao (Journal of Business Research, 2025)
Prior literature has reported a tendency for consumers to rate peer-to-peer (P2P) services more positively than the same services provided by traditional businesses (e.g. Airbnb vs. hotel). We first show that consumers experience greater empathy toward a P2P service provider (a person) than a traditional service provider (a business). We then show that P2P services enjoy higher evaluations because empathy for the provider leads consumers to tolerate minor negative elements in those settings as compared to traditional business settings. Further, we show that this effect is moderated by the perceived size of the business. The implications of this type of rating bias on traditional businesses and consumer welfare, and the limitations of this research, are discussed. © 2025 Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Online-reviews; Peer-to-peer; Rating-bias; Willingness-to-tolerate; dept.mrk

Are charitable gifts truly appreciated by the recipients who requested them? Impact of gift type and amount on recipients’ appreciation - Kang, In-Hye; Kim, Hyoseok (Journal of Business Research, 2025)
• For requested gifts during rite-of-passage occasions, appreciation for charitable vs. recipient-benefiting gifts depends on gift amount. • For low gift amounts, recipients appreciate charitable gifts more than recipient-benefiting gifts. • For moderate to high gift amounts, appreciation is similar between charitable and recipient-benefiting gifts. • In distant (vs. close) giver-recipient relationships, the effect of gift type on appreciation for low amounts is attenuated. • When gifts are not requested, recipients appreciate charitable gifts less than recipient-benefiting gifts. Requests for charitable cash gifts during rite-of-passage occasions (e.g., weddings) are becoming increasingly common. This research examines whether recipients’ appreciation differs depending on whether a requested cash gift is charitable (e.g., donating to support people in need) or recipient-benefiting (e.g., renovating the recipient’s kitchen). Across five studies, we find that the effect of the gift type on appreciation is moderated by the gift amount. For low amounts, recipients appreciate charitable gifts more than recipient-benefiting gifts. However, for moderate and high amounts, appreciation is similar across gift types. This effect is mediated by the recipients’ perception of whether the gift amount meets their expectations and their subsequent perception of thoughtfulness. Consistent with our mechanism, in distant giver-recipient relationships, the effect of the gift type on appreciation for low amounts is attenuated. When gifts are not requested, recipients appreciate charitable gifts less than recipient-benefiting gifts.
Keywords: Advertising; Business; Charitable gifts; Charitable giving; Conflict of interest; Donation; Economic growth; Economics; Finance; Gift appreciation; Gift giving; Gift price; Gift-giving; Marketing; Psychology; Social psychology; dept.mrk; peer-reviewed

Moral Disengagement, Machiavellianism and Academic Dishonesty - Prince, Melvin; Wang, J.; Priporas, Constantinos‐Vasilios (Journal of Academic Ethics, 2025)
Keywords: Academic Dishonesty; Academic dishonesty; Big Five personality traits; Cheating; Deviance; Dishonesty; Educational Research; Machiavellianism; Machiavellianism; Social Cognitive Theory; Moral Development; Moral Disengagement; Moral Philosophy and Applied Ethics; Moral Psychology; Moral disengagement; Morality; Personality; Psychology; Social psychology; Students; dept.mrk; peer-reviewed

Sensemaking and sustainability: a sensemaking perspective on the ethical use of big data in marketing strategizing - Wang, Emma (Junhong); Berthon, Pierre; Su, Yiran (Sustainable Development Seen Through the Lenses of Ethnoeconomics and the Circular Economy, 2024)
Despite the ethical concerns over the datafication and surveillance of individuals and groups, companies are making ever greater investments in big data. The assumptions underpinning this movement are: (1) organizations are passive implementers of big data—more data is the inevitable consequence of technology and a competitive necessity for business, (2) more data offers a more objective and accurate picture of reality and (3) more data enables better prediction. We argue that this perspective is strategically unsustainable and abdicates ethical responsibility.
Keywords: Big Data; Organization; Sensemaking; Strategizing; Sustainability; dept.mrk

Shopper Search in Response to Conditional Promotions: A Function of Basket Sizes and Incentive Types - Kulkarni, Atul; Yuan, Hong (Psychology and Marketing, 2025)
Keywords: Advertising; Business; Computer science; Consumer Attitudes; Consumer Behavior; Economics; Function (biology); Incentive; Incentives; Mathematics; Microeconomics; Shopping; dept.mrk; peer-reviewed

The impact of generative AI on syllabus design and learning - Kim, Hyoseok; Koo, Thomas K. B. (Journal of Marketing Education, 2024)
This research examines the impact of generative artificial intelligence (AI) on the perception of educational content quality, specifically by comparing AI-generated and human-generated course syllabi in marketing education. Results from four studies indicate a general preference for AI-generated syllabi, attributed to their greater perceived objectivity. This preference is more pronounced in conventional courses but diminishes in unconventional ones, suggesting that the unique aspects of these courses may reduce the advantages of generative AI. In addition, disclosing the AI authorship of syllabi significantly affects their perceived quality negatively, underscoring the impact of transparency on the acceptance of AI-generated educational materials. These findings highlight the potential of generative AI in educational content creation and its limitations in certain contexts. They offer valuable insights for enhancing educational practices and shaping policy decisions to enrich student experiences in the era of AI integration.
Keywords: dept.mrk; peer-reviewed

Political Polarization: Challenges, Opportunities, and Hope for Consumer Welfare, Marketers, and Public Policy - Weber, T.J.; Hydock, Chris; Ding, William; Gardner, Meryl; Jacob, Pradeep; Mandel, Naomi; Sprott, David E.; Van Steenburg, Eric (Journal of Public Policy & Marketing, 2021)
Political polarization is a marked political division in the population, characterized by multiple manifestations. The authors argue that it can affect consumer psychology, which in turn influences marketers, policy makers, and consumer welfare. The present work introduces the construct of political polarization to the marketing literature and shows how it serves as a novel challenge for various marketing stakeholders. For consumers, the authors propose that political polarization increases the salience of political identities, alters inter- and intragroup dynamics, and amplifies cognitive biases. These effects negatively affect consumer welfare, including financial welfare, relationships, mental and physical health, and societal interests. For marketers, polarization introduces a challenge to both be more sociopolitically engaged while also navigating competing political interests. Polarization also creates new opportunities and challenges for segmentation, targeting, loyalty, and product offerings. For policy makers, political polarization creates policy gaps, impedes the implementation of policy, and obstructs governance. Building from these insights, the authors consider the drawbacks and overlooked benefits of political polarization, potential remedies, and directions for future research.
Keywords: dept.mrk; peer-reviewed

Threat appraisal, emotional contagion, and Fear of COVID-19: Revision of the Extended Parallel Process Model - Prince, M.; Kim, Y. (Journal of Applied Social Science, 2023)
Fear of COVID-19 has been understandably widespread, given continual exposure to dire information from pandemic media coverage and interpersonal communications. The present study addresses a limitation of the extended parallel process model in predicting fear of COVID-19 by inclusion of the concept of emotional contagion. The main gap in the literature is filled by the study’s distinctive contribution that broadens and upgrades the extended parallel process model. The model is extended by its integration with the theory of emotional processing. The study is based on a national panel of adults (N = 206). The methods include path modeling by SmartPLS. In addition, multigroup analyses examine overall model differences between gender classifications. Findings and conclusions can be used to minimize excessive fear, and at the same time to promote confidence in following official public guidance and protective regulations to cope with the pandemic. © The Author(s) 2023.
Keywords: cognitive; dept.mkt; emotional contagion; fear; motivation; peer-reviewed; threat appraisal

Secondary Risk in COVID-19 Vaccination Intentions: A Theoretical Contribution to the Protection Motivation Paradigm - Prince, Melvin; Kim, Young (Journal of Applied Social Science, 2023)
This study presents an original model that features the emotion of fear of COVID-19 as a direct effect on vaccination intentions. A central research question addressed in the study is what roles do the emotion of fear of contracting COVID-19 and the threat posed by uptake of the COVID-19 vaccination play in levels of vaccination intention? The study used a structural equation model (SEM) and applied the SmartPLS 3.2.6 data analysis tool for model estimation and multivariate analysis variables. A key finding is that vaccination resistance is strongest when fear of COVID-19 is lower, and vaccination threat higher. Vaccination threat appraisal and vaccination intention were found to have a negative relationship. Response costs at higher levels lessen motivation for COVID-19 vaccination. Research implications include research-based targeting of differing segments by their primary fear, either fear of COVID-19 or of the preventative vaccine.
0 citations (Crossref) [2023-10-31]
Keywords: dept.mkt; peer-reviewed

Ethical marketing AI? A structured literature review of the ethical challenges posed by artificial intelligence in the domains of marketing and consumer behavior - Su, Y.; Wang, E.; Berthon, P. (Proceedings of the Annual Hawaii International Conference on System Sciences, 2023)
With the increasing use of AI in marketing, ethical repercussions are beginning to emerge. From privacy issues, through discrimination of marginalized groups, to emergent systemic social distortions, AI is changing the marketing ethical landscape. In this paper we conduct a structured literature review of the emerging ethical issues posed by AI in the domains of marketing and consumer behavior. We identify three clusters of ethical issues (algorithm, society and existential) and map these to the marketing domains of systems, brands, and consumers. We conclude that the field of ethical marketing AI is still very much in its infancy, but such is the rate of development ethical marketing AI is likely to become an important field for academics and practitioners alike. © 2023 IEEE Computer Society. All rights reserved.
Keywords: AI; Consumer Behavior; Ethics; Marketing; dept.mkt

Does polarizing personality matter in influencer marketing? Evidence from Instagram - Koorank Beheshti, Mohammadali; Gopinath, Mahesh; Ashouri, Sama; Zal, Saeed (Journal of Business Research, 2023)
Social media platforms have become more polarizing with the emergence of polarizing influencers. This research investigates how polarizing influencers can improve the effectiveness of brand-posts with the help of three experiments and field-data from Instagram. The results of the first experiment suggest that the polarizing nature of the communication source triggers defensive motivated reasoning among fans, even when the message being communicated is non-polarizing. This, in turn, has downstream consequences on post engagement and purchase intention. Analysis of 779 brandposts of Instagram influencers suggests that the polarization effect on post engagement is stronger for mega (vs. macro) influencers. By exploring the role of motivated reasoning, this research expands our understanding of the factors that drive consumers to engage with brand content on social media. The findings suggest that marketers can take advantage of the existing polarization among online users regarding polarizing influencers to enhance the effectiveness of their brand communication.
0 citations (Crossref) [2023-10-31]
Keywords: Defensive motivated reasoning; Group polarization; Influencer marketing; Source characteristics; dept.mkt; peer-reviewed

Metaphor elicitation: A new way to assess organizational culture - Prince, M.; Forr, J. (Psychologist-Manager Journal, 2021)
The purpose of this paper is to advance breakthrough research that further extends, as well as enrichens, our understanding of organizations. This is a companion article to “CEO Archetype Identity Drives Organization Culture” previously published in this journal. Archetypes are merely a special case of metaphors. In this paper, we generalize the concept of leadership archetypes to organization metaphors, adding original dimensions to existing concepts and theories of organizational diagnosis. Thus, the present research brings a new enlightening perspective to this field. Data from the past organization studies featured in this article involve the Zaltman Metaphorical Elicitation Technique (ZMET) embedded in qualitative in-depth personal interviews. These studies explore the impact of management styles on organization structure and functions. In each study metaphors were elicited from leaders and followers, and generated insights and action-oriented strategies to meet organizational challenges © 2021. American Psychological Association
2 citations (Crossref) [2023-10-31] tex.author_keywords: Archetypes; Leadership; Metaphor elicitation tex.document_type: Article tex.source: Scopus
Keywords: dept.mkt; peer-reviewed

A longitudinal reliability study of a consumer disidentification model - Prince, M.; Kwak, L. (Journal of Empirical Generalisations in Marketing Science, 2022)
Josiassen (2011) in a single cross-sectional survey investigated causal relations between consumer disidentification and domestic product judgments. The primary purpose of this replication paper is to evaluate the reliabilities of construct levels, as well as the significance, direction and magnitude of causal effects advanced in the original published structural model. The study measures relations between consumer disidentification (CDI) and domestic product judgments of American products over an extended 16 months period among second generation immigrants. In the present research the original CDI model fit was found to be longitudinally consistent and stable. Serendipitously, findings of the present study disclosed that over time baseline levels of consumer disidentification vary and actually declined significantly. Additionally, the negative effect of consumer disidentification on American product judgments significantly weakened over the course of the study. As an additional test of consumer predisposition reliability over time, the model in this study incorporated consumer xenocentrism (XEN) as a second predictor variable of domestic product judgments. Findings of this analysis were consistent with those found for CDI. These new phenomena have important theoretical and managerial implications. © 2022, University of South Australia. All rights reserved.
tex.author_keywords: Consumer disidentification; Ethnic identity and acculturation; Xenocentrism tex.document_type: Article tex.source: Scopus
Keywords: dept.mkt; peer-reviewed; ⛔ No DOI found

The effect of mindfulness on service encounter quality - Wang, Emma Junhong; Berthon, Pierre R.; Bechwati, Nada Nasr (Journal of Services Marketing, 2020)
Purpose This paper aims to explore the effect of employees’ state mindfulness, a short period of mindful presence, on the quality of the service they provide in a service encounter. Design/methodology/approach Three studies are conducted. A pilot study explores the relationship between state mindfulness and service encounter quality. Experiment 1 examines whether a 15-min mindfulness exercise results in an increase in service employees’ state mindfulness. Experiment 2 tests whether induced state mindfulness produces higher service quality and whether a reminding technique can prolong state mindfulness between service encounters. Findings The results demonstrate the following. First, that more mindful employees provide better service quality. Second, that a short, easily implemented, mindfulness exercise can reliably increase employees’ state mindfulness. Third, induced mindfulness has an impact on subsequent service quality in terms of reliability, assurance, empathy and responsiveness. These effects persist regardless of the service encounter structure (high vs low structure) or the degree of emotional labor involved (high vs low emotionally charged). Finally, the reminding technique developed as part of this research suggests that state mindfulness can be maintained between service encounters. Research limitations/implications As simulated (programmed) customers are used, independent evaluators to assess service quality are used. Service providers in this study are college students; future field studies should consider a wider range of service providers. The research focuses on state mindfulness; exploration of trait mindfulness offers future research opportunities. Originality/value To the best of the authors’ knowledge, this research is the first to empirically examine the link between mindfulness and service quality. It shows that mindfulness can be induced, and through a reminding technique be maintained, and improve service quality across service interactions. This is a powerful finding for marketing managers, for it offers a new method to enhance service provision. Moreover, this research implies that the increase in service quality is likely to be accompanied by reduced job burnout: a double win for employees, employers and customers.
7 citations (Crossref) [2023-10-31]
Keywords: Emotional labor; Induced state mindfulness; Mindfulness; Service encounter quality; Service encounter structure; dept.mkt; peer-reviewed

Exploring the optimized social advertising strategy that can generate consumer engagement with green messages on social media - Kyu Kim, Young; Yim, Mark Yi-Cheon; Kim, Eunjin; Reeves, William (Journal of Research in Interactive Marketing, 2020)
Purpose: Given that many consumers are skeptical about environmentally based advertising campaigns, the purpose of this study is to propose an optimized message strategy to facilitate consumer engagement with green messages in social media contexts. Design/methodology/approach: Four empirical studies are conducted using self-report questionnaires to test proposed hypotheses with a focus on the interplay between claim specificity and benefit appeals in green advertising on social media. Findings: The current study examines the interaction effects of claim specificity and benefit appeals on consumer engagement in social media. Specifically, the results reveal that when the message claim is abstract, using other-benefit appeals produces more positive consumer engagement than using self-benefit appeals. Moreover, the results illustrate that self-enhancement motivates consumers to engage with green product advertising messages when the advertising appeal is abstract and the advertising message is associated with benefits for others. Finally, it is found that consumers’ self-construal level moderates the interaction effect of claim specificity and benefit appeals type on consumer engagement on social media. Practical implications: This paper has practical implications to both social media managers and advertisers in the green product industry: a match with advertising claim specificity and construal level (i.e. social distance: self-benefit vs other-benefit) should be ensured to increase consumer engagement on social media. In addition, self-enhancement and self-construal should be considered for a better message strategy in social media contexts. Originality/value: The findings make important contributions to the literature in that we extend the applications of construal level theory to social media contexts as a valid theoretical tool to identify optimized green message strategies. As such, it provides future researchers and practitioners in the domain of green campaigns with useful guidelines to boost more consumption of green products. © 2020, Emerald Publishing Limited.
29 citations (Crossref) [2023-10-31] WOS:000607792100001
Keywords: Online consumer behavior; Social media advertising; dept.mkt; peer-reviewed

Impact of risk aversion, reactance proneness and risk appraisal on travel destination risk perception: - Prince, Melvin; Kim, Young Kyu (Journal of Vacation Marketing, 2021)
The aim of the study is to investigate the motivational effects of tourist traits and risk appraisal on tourist destination risk perception. Risk appraisal involves subjective estimates of vulnerability to a threat and the threat’s consequential severity. Fear levels influence both of these elements of risk appraisal. Individual differences in reactance proneness and risk aversion are introduced into the study model to more fully account for differences in travel destination risk perceptions. The study design involves US adults, who have used their passports for international travel in the past 5 years. Travel risk assessments were studied for four destination sites: London, Tokyo, Kuala Lumpur and Istanbul. A general structural model is developed to test hypotheses about antecedents and consequents of risk appraisal and destination risk perception. © The Author(s) 2021.
2 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85100166276
Keywords: dept.mkt; peer-reviewed

Cultural adaptation and consumer disidentification in the us - Prince, M.; Kwak, L (Journal of Empirical Generalisations in Marketing Science, 2020)
Alexander Josiassen (2011) initiated research on the consumer disidentification (CDI). More specifically, in his investigation of 2nd generation Turks in the Netherlands, he introduced the concept of acculturation as an antecedent to consumer disidentification among this ethnic group. Josiassen's study showed that acculturation negatively affects CDI. The present replication research among American 2nd generation US immigrants confirmed Josiassen’s findings with respect to CDI. It also confirmed his findings that acculturation positively affects consumer ethnocentrism (CET). In elaborating his model, the US study found that (a) national disidentification (NDI) is inversely predictive of acculturation, and (b) acculturation is negatively predictive of consumer xenocentrism (XEN). Replication of the Netherland CDI model in the U.S. results in an acceptable measurement fit and structural fit. © 2020, University of South Australia. All rights reserved.
Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85096865217
Keywords: Consumer disidentification; Cross-cultural; Ethnocentrism; National disidentification; Xenocentrism; dept.mkt; peer-reviewed; ⛔ No DOI found

Consumer responses toward symmetric versus asymmetric facial expression emojis - Hewage, G.S. Urumutta; Liu, Yue; Wang, Ze; Mao, Huifang (Marketing Letters, 2021)
Facial expression emojis are commonly used in digital communications and marketing campaigns. However, it is less known how the design of emojis may affect consumer responses. To address this gap, this research examines the impact of emojis’ facial asymmetry levels on consumer judgments. Findings across four studies demonstrate that compared with their symmetric counterparts, asymmetric facial expression emojis are more likely to receive favorable consumer evaluations. This effect is driven by perceptions of human expression resemblance and emotional expression strength and tends to be more prominent among consumers with a higher level of emotional sensitivity. Moreover, marketing messages including an asymmetric (vs. a symmetric) emoji are more likely to generate positive consumer responses.
8 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85094917562
Keywords: dept.mkt; peer-reviewed

Genetically modified crops’ environmental impact and trust in eco-labels - Kwak, Lynn E.; Yoon, Sang Won; Kim, Younjun (Australasian Marketing Journal, 2020)
The U.S. Department of Agriculture expects companies to disclose genetically modified (GM) ingredients in foods and beverages by January 2022. While food companies fear that the stigma of GM labels could cause GM food sales to decline, eco-labeling could lessen the impact of GM-labeling. The results of the present research indicate that neither the eco-labeling alone nor the eco-labeling accompanied by information about the environmental benefits of GM crops influence consumers’ willingness to buy. Based on the mediation analysis, however, trust of eco-labels mediates the relationship between GM foods’ environmental friendliness information and consumers’ willingness to buy eco-labeled GM food. The theoretical and practical implications of the findings are discussed. © 2020
4 citations (Crossref) [2023-10-31] tex.ids: kwakGeneticallyModifiedCrops2020a
Keywords: Eco-labeling; Genetically modified (GM) foods; Trust; Willingness to buy; dept.eco; dept.mkt; peer-reviewed

Domestic Product Involvement and Consumer Willingness to Buy Domestic Products: Empirical Testing of a Cognitive Consistency Theory Framework - Prince, Melvin (Journal of International Consumer Marketing, 2020)
This study investigates biases affecting domestic products willingness to buy (WTB). An interdisciplinary perspective uses the cognitive consistency theory as the framework for the development of a new model. The model includes domestic product involvement (DPI). The impact on WTB is predicted by consumer ethnocentrism, and product judgment, driven by DPI are tested with survey data from an adult sample of 255 UK consumers. The study concludes with observations about the value of research findings for marketing practice. © 2020 Taylor & Francis Group, LLC.
7 citations (Crossref) [2023-10-31] WOS:000517943000001
Keywords: Cognitive consistency theory; consumer ethnocentrism; dept.mkt; domestic product involvement; peer-reviewed; product judgment; willingness to buy

Does the Netherlands-based consumer disidentification model work in the US? - Prince, Melvin; Kwak, Lynn (EMPGENS | Journal of Empirical Generalisations in Marketing Science, 2020)
Alexander Josiassen (2011) initiated research on the consumer disidentification (CDI) concept and its impact on product purchase behavior. In his investigation, a predictive model that included CDI as an exogeneous factor in domestic product preference was tested on adult second-generation immigrants who were born in, and lived in, the Netherlands. The model also incorporated consumer ethnocentrism (CET) as a second predictor variable. Josiassen's study showed that CDI negatively affected the purchase of products made domestically or by domestic firms. Conversely, CET was found to have a positive effect on the purchase of these products. Furthermore, relationships of CDI and CET to purchase intentions were independent of each other. In the Netherlands model, both variables were hypothesized to explain domestic product preference directly and indirectly through domestic product judgment. This paper replicates and assesses the generalizability of the CDI construct and model. Replication of the Netherland CDI model in the U.S. results in an acceptable measurement fit, but a slightly below acceptable structural fit. © 2020, University of South Australia. All rights reserved.
tex.ids: princeDoesNetherlandsbasedConsumer2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85091584869 type: Article
Keywords: Consumer disidentification; Cross-cultural; Domestic product preference; Ethnocentrism; Second-generation immigrants; dept.mkt; peer-reviewed; ⛔ No DOI found

The psychology of consumer ethnocentrism and cosmopolitanism: a five-country study of values, moral foundations, gender identities and consumer orientations - Prince, Melvin; Yaprak, Attila; Cleveland, Mark; Davies, Mark A. P.; Josiassen, Alexander; Nechtelberger, Andrea; Nechtelberger, Martin; Palihawadana, Dayananda; Renner, Walter; Supekova, Sona Chovanova; Von Wallpach, Sylvia (International Marketing Review, 2020)
Purpose: The purpose of this paper is to examine the extent to which personal values, moral foundations and gender-role identities affect, in sequence, consumers' constructions of their ethnocentric and cosmopolitan orientations. Achieving a better understanding of the psychological makeup of consumer ethnocentrism and cosmopolitanism should help managers better design international market segmentation and brand positioning strategies. Design/methodology/approach: The study's conceptual framework is anchored in attitude and values theories, and focuses on the social categorizations that consumers make and how these contribute to the formation of their ethnocentric and cosmopolitan orientations. Drawing data from consumers living in five European countries, we test our theoretical conjectures through structural equation modeling approaches, including multigroup analysis at the country level, as well as the identification and scrutiny of potential pan-European consumer segments. Findings: Findings show that personal values, moral foundations and gender-role identities do exert direct and indirect (partially mediated) effects on the formation of consumers' ethnocentric and cosmopolitan orientations. These provide numerous insights for managers in terms of how they can segment domestic and international markets, as well as how to position products and communicate brand strategies. Research limitations/implications: The study focused on consumers' personal and role identities and offers implications based on data gathered from a sample of five European countries. Future work should broaden this perspective by including other identity facets, such as religious and ethnic identities, as well as product-category and brand-specific outcomes, in order to help develop a more comprehensive picture of the psychology underpinning consumers' identity-related orientations, and their effects on consumer behavior. Future research should also study these issues in a broader geographical context, by including national markets that have culturally diverse populations as well as places with dissimilar cultural and economic profiles. Originality/value: The study shows that individuals' personal values, moral foundations and gender roles have a strong effect on the formation of consumer ethnocentrism and consumer cosmopolitanism orientations. Consideration of how these antecedent constructs operate in concert to shape consumers' in- versus out-group orientations has been overlooked in the international marketing literature. Beyond the ramifications for theory, the study offers numerous substantive managerial implications in terms of how consumers are likely to respond to local and global/foreign products/brands based on these orientations. © 2020, Emerald Publishing Limited.
18 citations (Crossref) [2023-10-31] WOS:000537142600001
Keywords: Consumer cosmopolitanism; Consumer ethnocentrism; Gender role identity; International market segmentation; Moral foundations; Values; dept.mkt; peer-reviewed

How to easily facilitate consumers’ mental simulation through advertising: the effectiveness of self-referencing image dynamics on purchase intention - Yim, Mark Yi-Cheon; Kim, Young K.; Lee, JeongGyu (International Journal of Advertising, 2020)
10 citations (Crossref) [2023-10-31] tex.ids: yimHowEasilyFacilitate2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85088955581 type: Article
Keywords: dept.mkt; peer-reviewed

Mindful consumption: Three consumer segment views - Milne, George R.; Ordenes, Francisco Villarroel; Kaplan, Begum (Australasian Marketing Journal, 2020)
As consumers are moving away from mindless consumerism, a mindful consumption literature has emerged that is based on Buddhist and psychological perspectives of mindfulness. While the idea of mindful consumption has great potential, there is little empirical research to date that comprehensively examines the consumer perspective on the role of mindfulness on consumption. To provide a grounded consumer perspective, the authors segment mindful consumption views from open-end text using a mixed method of clustering and text mining. By analyzing the segmentation structure, the authors discover various consumer views of mindful consumption, such as careful economic based consumption, monitoring activities of firms, and being informed about the impact of consumption choices. The authors compare the empirical results with the academic literature to provide directions for future research. © 2019 Australian and New Zealand Marketing Academy
40 citations (Crossref) [2023-10-31] tex.ids: lens.org/017-626-502-015-133, milneMindfulConsumptionThree2020a, pop00147 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85072713622 tex.type: [object Object] type: Article
Keywords: Mindful consumption; Mindfulness; Segmentation; Sustainability; Text mining; dept.mkt; peer-reviewed